Integrative Taxonomy of Tereancistrum spp. (Monopisthocotyla: Dactylogyridae) Parasites of the Gills of Freshwater Fishes from the Caatinga Domain, Brazil - de Oliveira Fadel Yamada, Priscilla; de Sousa, Wallas Benevides Barbosa; Ebert, Mariana Bertholdi; Diniz, Maria Fernanda Barros Gouveia; Tavares-Dias, Marcos; Silva, Reinaldo José da; Yamada, Fabio Hideki (MDPI, 2025)
Tereancistrum is a common genus of Neotropical monopisthocotylans; however, information on its diversity and phylogeny remains limited. In this study, we describe four new species of Tereancistrum parasitizing the gills of Prochilodus brevis (Characiformes: Prochilodontidae) from a weir in the state of Ceará, Brazil. Tereancistrum spiralocirrum n. sp. and Tereancistrum scleritelongatum n. sp. are characterized by a dextro-ventral vaginal pore and a Y-shaped dorsal bar. Notably, Tereancistrum spiralocirrum n. sp. is the first species in the genus to possess a male copulatory organ (MCO) with multiple rings (16 to 18). In contrast, Tereancistrum ancistrum n. sp. and Tereancistrum kritskyi n. sp. are distinguished by a sinistral vaginal pore, a sclerotized MCO in the form of a coiled tube with slightly more than one clockwise ring, and an accessory piece that is non-articulated with the base of the MCO. However, Tereancistrum ancistrum n. sp. is unique in lacking a dorsal bar. Sequences of the LSU rDNA obtained from seven species of Tereancistrum parasitizing P. brevis and Leporinus piau, along with published sequences of other Dactylogyridae members, were included in the molecular analyses. Phylogenetic reconstructions supported the monophyly of Tereancistrum.